Enhanced performance of the tangerines-like CuO-based gas sensor using ZnO nanowire arrays. (1st November 2020) - Cai, Lina; Li, Hairong; Zhang, Huan; Fan, Wenhao; Wang, Jianan; Wang, Yongchang; Wang, Xudong; Tang, Ying; Song, Yuzhe
Abstract: In this work, sensors based on the ZnO nanowire arrays/CuO nanospheres heterostructure were prepared by using the simple low temperature hydrothermal method. X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (HRTEM) and energy dispersive spectrometry (EDX) were used to characterize the crystal phase, structure and surface morphology of the as-prepared samples, respectively. The sensing characteristics of the as prepared samples were systematically measured. Obviously, the sensors based on the ZnO/CuO heterostructure exhibited excellent sensor parameters than pure CuO nanospheres. The response value of the ZnO/CuO heterostructure sensor with the growth time of 5 h (ZC-2) to 100 ppm of ethanol gas is up to 55.4 at 122 °C, which is about 8.8 fold and 3.4 fold more than that of pure CuO nanospheres (R = 6.3) and ZnO nanowire arrays (R = 16.4), respectively. In addition, the ZC-2 sensor exhibits the excellent selectivity for ethanol compared to other test gases. Significant improvement of the gas sensing characteristics was related to the formation of n-p heterojunction. The prepared ZC-2 gas sensor exhibits broad application prospects in the detection of ethanol. Highlights: Orange-like CuO-based gas sensor decorated with ZnO nanowire arrays were fabricated. The preparation route was relatively facile, simple and low energy consumption. The ZnO nanowire arrays/CuO nanospheres heterostructure gas sensor shows a high response towards ethanol gas. The construction of 3D heterostructure provides an effective way to develop high-performance gas sensors.